Differential and long-term language impact on math. (October 2016) - Chen, Fang; Chalhoub-Deville, Micheline
Literature provides consistent evidence that there is a strong relationship between language proficiency and math achievement. However, research results show conflicts supporting either an increasing or a decreasing longitudinal relationship between the two. This study explored a longitudinal data and adopted quantile regression analyses to overcome several limitations in past research. The goal of the study is to detect more accurate and richer information on the long-term relationship between language and math, taking into consideration the socioeconomic status, gender, and ethnicity background at the same time. Results confirmed a persistent relationship between math achievement and all the factors explored. More importantly, it revealed that the strength of the relationship between language and math differed for students with various abilities both within and across grades. Model comparison suggests that language demand contributes to the achievement gap between ELLs and non-ELLs in math. There also seems to be a disadvantage for the geographically isolated group in academic achievement. Interpretation and implications for teaching and assessment are discussed.